2016
DOI: 10.18632/oncotarget.9744
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 sustains self-renewal and invasiveness of glioma-initiating cells

Abstract: Glioblastoma multiforme (GBM) is the most common type of brain tumors with dismal outcomes. The mesenchymal phenotype is the hallmark of tumor aggressiveness in GBMs. Perivascular smooth muscle cells (pericytes) are essential in homeostasis of normal and glioma tissues. Here we found HMGA2, an architectural transcription factor that promotes mesenchymal phenotypes in a number of solid tumors, is highly expressed in mesenchymal subtype of GBMs and labels both glioma pericytes and glioma-initiating cells (GICs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Several reporter systems to study endogenous promoter activation by HMGA2 have previously been reported (22,23). We fortuitously discovered that in HeLa cells, which do not express detectable levels of endogenous HMGA2, C-terminally FLAG-tagged human HMGA2 significantly enhanced Renilla luciferase expression from a reporter gene driven by the herpes simplex virus thymidine kinase (HSV-TK) promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Several reporter systems to study endogenous promoter activation by HMGA2 have previously been reported (22,23). We fortuitously discovered that in HeLa cells, which do not express detectable levels of endogenous HMGA2, C-terminally FLAG-tagged human HMGA2 significantly enhanced Renilla luciferase expression from a reporter gene driven by the herpes simplex virus thymidine kinase (HSV-TK) promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, TF HMGA2 was found to be expressed in both GSCs and pericytes of GBM. Depletion of HMGA2 in GSCs abrogates their potential for pericyte differentiation, indicating its role in self-renewal properties of GSCs (Zhong et al, 2016). …”
Section: The Microenvironment Of Gscs: the Tumor Vascular Nichementioning
confidence: 99%
“…C). It was previously shown that Lin28 located upstream of HMGA2 can upregulate HMGA2 (Mao et al ., ) and that HMGA2 promotes GB stem cell renewal and tumor initiation in GB cells (Zhong et al ., ). In concordance with the Dov‐mediated reduction in cellular Lin28 and HMGA2 levels, we showed that Dov reduced the number of GB spheres in a concentration‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Our data in GB cells showed that Dov downregulates the stem cell factor and RNA‐binding protein Lin28A and its target HMGA2, identifying a hitherto unknown role of Dov as an inhibitor of the LIN28/Let‐7/HMGA2 axis in human GB. In agreement with the well‐known function of HMGA2 in promoting self‐renewal of stem cells (Zhong et al ., ) and GB tumor initiation capability (Kaur et al ., ), Dov attenuated GB sphere formation and increased apoptosis in sphere‐forming GB cells. HMGA2 expression is controlled by specific Let‐7 microRNA members that bind to the 3′UTR of HMGA2 to cause reduced mRNA stability and translation (Hammond and Sharpless, ).…”
Section: Discussionmentioning
confidence: 99%